La portée constitutionnelle du préambule de l'Acte de l'Amérique du Nord britannique - Sormany, Louis (Les Cahiers de droit, 1977)
At its title indicates, the purpose of this article is to determine what the significance of the preamble of the British North America Act is; that is to say, what influence the preamble of the B.N.A. Act can have in the interpretation of that law. In the first part of this article, Mr. Sormany discusses the fundamental points necessary for the study of the subject, i.e., the formal nature of the preamble of the B.N.A. Act, the analysis of its text, and the interpretation given it by the courts. . . In the second part, he discusses the focal point of his paper — the constitutional importance of the preamble of the B.N.A. Act.More precisely, Mr. Sormany considers that the preamble of the B.N. A. Act can only have an importance that is essentially interpretation in nature. This is derived from the fact that it is no more than the preamble of a law and that, because of that, its significance is limited.Then the analysis of the text of the preamble of the B.N.A. Act makes it possible to determine the exact significance of each of its four paragraphs, and to decide which of these are susceptible of having some significance. For example, in the course of this analysis the author explains that the part of the preamble of the B.N. A. Act which mentions the Constitution of the United Kingdom implies that the Constitution of Canada incorporates the principle of the supremacy of parliamentary law, that is, a fusion of the sovereignty of parliament and of the Rule of Law. Mr. Sormany also explains why, according to him, certain parts of the preamble of the B.N.A. Act, such as the third and fourth paragraphs, are not of constitutional significance.Finally, the author completes this first section with a review of the jurisprudence relative to the preamble of the B.N.A. Act. The purpose of this review is to indicate in which cases and in what fashion the preamble of the B.N.A. Act has been invoked. Therefore, this review is not an analysis of this body of jurisprudence. The analysis of the most important cases appears in section 2. Nevertheless, this review permits one to determine that the preamble of the B.N.A. Act was not invoked only as an affirmation of certain civil liberties (Reference re Alberta Statutes,Saumur, Switzman, Hess, etc. . .) but also, for example, as a reference to the principle of parliamentary supremacy (Persons' Case), and as a recognition of the status and powers of the Lieutenant-governor (In re TheInitiative and Referendum Act).At the start of the second section, Mr. Sormany focuses on the parts of the preamble, which are susceptible of having constitutional significance in the light of his discussions in section 1. According to him, three points emerge from the preamble of the B.N. A. Act, and each of them is the subject of a sub-section.In the first sub-section, the author demonstrates that if one can perceive a reference to the theory of the pact, or to the Quebec and London Resolutions, in the preamble, then in none of its aspects can the preamble have a significance at the juridical level.On the other hand, in the second sub-section, Mr. Sormany concludes that, in spite of its apparent ambiguity, the part of the preamble which refers to the Constitution of the United Kingdom has a very important constitutional significance because it constitutes the only affirmation in the B.N.A. Act of one of its basic principles which is the principle of the supremacy of Parliamentary law. The author analyses why case law has given an entirely different significance to this part of the preamble, finding in it either an affirmation of certain civil liberties, the recognition of the status and of the powers of the Lieutenant-governor, or again, a reference to the principle of Ministerial responsibility and the independence of the courts.Finally, in the third sub-section, Mr. Sormany demonstrates that the preamble of the B.N. A. Act does not possess any constitutional significance in so far as the affirmation of the principle of federalism is concerned. This conclusion is based on the fact that the intent of the B.N.A. Act is sufficiently clear in that question and that the preamble does not add anyting in this respect.This study is thus an exhaustive analysis of the constitutional significance of the preamble of the B.N.A. Act, and it is on this basis that its originality is founded. In effect, although it is a question of a part of the B.N.A. Act which is susceptible of having some influence on constitutional law, and in spite of the declaration of principles which it makes, to date, the preamble of the B.N.A. Act has never itself been the subject of specific analysis.